IMF Staff papers : Volume 8 No. 2. - International Monetary Fund. Research Dept. (Washington, D.C. : International Monetary Fund, 1961)
This paper presents views of Professor Robert Triffin on international liquidity and the role of the IMF. The paper is an exposition of Triffin's diagnosis of present and prospective difficulties in the international financial area and of his prescriptions for dealing with these difficulties. It should be noted at the outset that Triffin has focused attention upon some major problems of international liquidity and international financial organization. His diagnosis of present and prospective difficulties, and his recommendations for meeting these difficulties, are acute and thought provoking. The expanded IMF is nowhere clearly directed to provide an adequate rate of growth of reserves, the prospective inadequacy of which is responsible for its being, nor is it told what an adequate rate of growth would be. The reader must conclude that Triffin proposes to expand the functions of the IMF and give it a full armory of central bank instruments, but that he is unwilling to provide it with an explicit statement of policy objective, let alone any specific guides to operations policy.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet